Dent disease: A cause of proteinuria against all odds - Rosinha, Inês; Machado, Marta; Cordinhã, Carolina; do Carmo, Carmen; Gomes, Clara (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Dent disease is a rare X-linked progressive renal disease characterized by hypercalciuria and low molecular weight proteinuria. In early childhood, patients may manifest only proteinuria and/or hypercalciuria, both of which are generally asymptomatic. The authors report three cases of male patients with asymptomatic, non-orthostatic nephrotic proteinuria first detected during screening for an acute condition. All had intermittent hypercalciuria, one had nephrocalcinosis, and one had mild hypotonia and some learning difficulties. Genetic testing identified pathogenic variants in all patients, two in the OCRL gene and one in the CLCN5 gene. To date, none have developed chronic kidney disease. The diagnosis of Dent disease can be challenging, but it should be considered in all men with unexplained proteinuria. This approach may not only allow for earlier diagnosis, but also avoid unnecessary testing and potentially harmful treatments.